Plant derived active compounds as potential anti SARS-CoV-2 agents: an in-silico study. Issue 21 (5th December 2022) - Kashyap, Dharmendra; Jakhmola, Shweta; Tiwari, Deeksha; Kumar, Rajesh; Moorthy, N. S. Hari Narayana; Elangovan, Manivannan; Brás, Natércia F.; Jha, Hem Chandra
Abstract: Plants are a valued potential source of drugs for a variety of diseases and are often considered less toxic to humans. We investigated antiviral compounds that may potentially target SARS-CoV-2 antigenic spike (S) and host proteins; angiotensin-converting enzyme2 (ACE2), and transmembrane serine protease2 (TMPRSS2). We scrutinized 36 phytochemicals from 15 Indian medicinal plants known to be effective against RNA viruses via molecular docking. Besides, the TMPRSS2 structure was modeled and validated using the SWISS-MODEL. Docking was performed using Autodock Vina and 4.2 followed by visualization of the docking poses on Pymol version 2.4.0 and Discovery Studio Visualizer. Molecular docking showed that 12 out of 36 active compounds interacted efficiently with S, ACE2, and TMPRSS2 proteins. The ADMET profile generated using the swissADME and pkCSM server revealed that these compounds were possessed druggable properties. The Amber 12 simulation package was used to carry out energy minimizations and molecular dynamics (MD) simulations. The total simulation time for both S protein: WFA and S protein: WND complexes was 300 ns (100 ns per replica). A total of 120 structures were extracted from the last 60 ns of each MD simulation for further analysis. MM-PBSA and MM-GBSA were employed to assess the binding energy of each ligand and the receptor-binding domain of the viral S-protein. The methods suggested that WND and WFA showed thermodynamically favorable binding energies, and the S protein had a higher affinity with WND. Interestingly, Leu455 hotspot residue in the S protein, also predicted to participate in binding with ACE2, was engaged by WND and WFA. Highlights: Plants' natural active compounds may aid in the development of COVID-19 therapeutics. MD simulation study revealed stable binding of withanolide D and withaferin A with spike protein Withanolide D and withaferin A could be effective against SARS-CoV-2 spike protein. Discovery of druggable agents that have less or lack of binding affinity with ACE2 to avoid the organs associated with comorbidities. According to ADMET selected phytochemicals may be used as druggable compounds. Communicated by Ramaswamy H. Sarma